Pengaruh bedside teaching model terhadap penguasaan kasus dan kemampuan ketrampilan mahasiswa praktik klinik keperawatan - Solikhah, Umi; Elsanti, Devita (Jurusan Keperawatan FIKES UNSOED, 2012)
Bedside teaching methods are used to know in depth and comprehensive review of all cases of patients being studied. Selection of appropriate methods for teaching clinical nursing at the hospital became urgent need for nursing education providers to obtain an appropriate learning outcomes with student competence. The aim of this research is to identifying differences in the influence of bedside teaching methods towards the case mastery and the skill capabilities of nursing student clinical practice between the control group and intervention group. Quasy experiments study was used in this research; with 25 samples of each group. Data was analyzed with independent t-test. The study has been found differences in the influence of bedside teaching methods to the case mastery of nursing clinical practice student between the control group and intervention group (p-value=0.001); but did not with the skill capabilities (p-value = 0.686). It should be used as guidance as clinical bedside teaching methods applied in conjunction with other methods to improve the competence of nursing students mastery of the case.